2005
DOI: 10.1093/glycob/cwj033
|View full text |Cite
|
Sign up to set email alerts
|

ST6GalNAc I expression in MDA-MB-231 breast cancer cells greatly modifies their O-glycosylation pattern and enhances their tumourigenicity

Abstract: Sialyl-Tn is a carbohydrate antigen overexpressed in several epithelial cancers, including breast cancer, and usually associated with poor prognosis. Sialyl-Tn is synthesized by a CMP-Neu5Ac:GalNAcalpha2,6-sialyltransferase: CMP-Neu5Ac: R-GalNAcalpha1-O-Ser/Thr alpha2,6-sialyltransferase (EC 2.4.99.3) (ST6GalNAc I), which transfers a sialic acid residue in alpha2,6-linkage to the GalNAcalpha1-O-Ser/Thr structure. However, established breast cancer cell lines express neither ST6GalNAc I nor sialyl-Tn. We have p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
158
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(174 citation statements)
references
References 33 publications
12
158
1
3
Order By: Relevance
“…Thus, previous studies have primarily focused on a limited type of glycosylation events that impart tumor cell properties. Some common alterations of glycosylation have shown to generally accompany with tumorigenesis and metastasis, such as, increase in branches of N‐linked oligoaccharides,7, 8 changed sialylation on certain proteins or antigens,5, 9, 10 abnormal biosynthesis of O‐linked oligosaccharides 11, 12. Owing to the complexity and variability of carbohydrate structures, the cancer‐associated carbohydrate chains have no general changed feature.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, previous studies have primarily focused on a limited type of glycosylation events that impart tumor cell properties. Some common alterations of glycosylation have shown to generally accompany with tumorigenesis and metastasis, such as, increase in branches of N‐linked oligoaccharides,7, 8 changed sialylation on certain proteins or antigens,5, 9, 10 abnormal biosynthesis of O‐linked oligosaccharides 11, 12. Owing to the complexity and variability of carbohydrate structures, the cancer‐associated carbohydrate chains have no general changed feature.…”
Section: Introductionmentioning
confidence: 99%
“…Human breast cancer cells show increased expression of sialyltransferase ST6GalNAc1, which can modify Tn to form sialyl Tn (sTn) (26,27). Therefore, deficiency of C1Galt1 may cause compensatory increase of sTn.…”
Section: Discussionmentioning
confidence: 99%
“…O-glycan biosynthesis ST6GALNAC1 Sialylation of O-glycans to produce the cancer-associated sTn antigen (Munkley 2016) Associated with poor prognosis in numerous cancer types (Munkley 2016). Promotes tumourigenicity and metastasis in breast and gastric cancer cells (Julien et al 2006, Ozaki et al 2012 ST6GALNAC1 shown to synthesise sTn and reduce cell adhesion in prostate cancer cells (Munkley et al 2015c, Munkley & Elliott 2016b. sTn antigen expressed in high grade prostate tumours (Myers et al 1994, Genega et al 2000.…”
Section: Figurementioning
confidence: 99%